11x-2+x-6=4(x+3)+8(x+12)

Simple and best practice solution for 11x-2+x-6=4(x+3)+8(x+12) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-2+x-6=4(x+3)+8(x+12) equation:



11x-2+x-6=4(x+3)+8(x+12)
We move all terms to the left:
11x-2+x-6-(4(x+3)+8(x+12))=0
We add all the numbers together, and all the variables
12x-(4(x+3)+8(x+12))-8=0
We calculate terms in parentheses: -(4(x+3)+8(x+12)), so:
4(x+3)+8(x+12)
We multiply parentheses
4x+8x+12+96
We add all the numbers together, and all the variables
12x+108
Back to the equation:
-(12x+108)
We get rid of parentheses
12x-12x-108-8=0
We add all the numbers together, and all the variables
-116!=0
There is no solution for this equation

See similar equations:

| 3x^2+76+88-2x^2=180 | | -10(n+5)=40 | | 1920=16t^2 | | 6-2y=3y+1 | | --5x16=9x+x-1 | | 7(x-9)+2=-61 | | -2x-3=3x-4-7x | | Y=6x^2+17x+12 | | d=5*19 | | 13y+19=6(9-y)+14 | | 200m-100m+475000=50500-150m | | 5*(x-4)=7x-83 | | 10m−8=8m+6 | | 5x(x-4)=7x-83 | | 22x-5+20x+7=180 | | 7(x-9)=2=-61 | | -3(9z+6)=-29-8z | | x=(-1) | | -23x2+92=0 | | 5(x-4)=7x-83 | | -72=-6-3(-5x+9) | | 3(x-2)^2+54=0 | | 3(3-7k)=-7(-1+3k)-1 | | f(-12)=11 | | -8.01+7.6c=18.39+14.2c | | 12b+9+5b=10(4b+9)-4(b+6) | | 18-1x=30-2x | | 4x=2{x-5}-2 | | 0.9p+14.35=14.35+0.9p | | 18-1x=5x+10 | | (4x+3)=(2×+5+5x) | | 8+2(8r-2r)=4(3r=2) |

Equations solver categories